LINGUOSTYLISTIC FEATURES OF GRAPHIC EXPRESSIVE DEVICES IN J. D. SALINGER’S NOVEL THE CATCHER IN THE RYE. - Kushakova Nodira Odilovna (International Journal of Literature and Language Studies, 2026)
The aim of this study is to identify the methods used to render graphic expressive devices in the translation of J. D. Salinger’s novel “The Catch in the Rye” and to analyze their functional characteristics. During the research, cases of preserving typographic emphasis, conveying it through linguistic compensation, and omitting it in translation were examined on the basis of a comparative analysis.